Berpikir Kreatif dan Motivasi Belajar Pada Pembelajaran Menggunakan Problem Based Learning - Shamdas, Gamar B. N.; Rede, Amram; Bustamin, Bustamin (Jurnal Kreatif Online, 2020)
Problem-based Learning (PBL) is a learning method that can change the behavior of students who passively receive information to actively seek information. However, the implementation of PBL is not in accordance to its character, causing boring learning conditions, as happened in Grade VII students of SMP Negeri 4 Palu in science subject. The purpose of this research was to improve students' creative thinking and learning motivation through the implementation of PBL in science subject in Grade VII of SMP Negeri 4 Palu. This research used a quasi-experimental method with quantitative and qualitative approaches. The research design was a pretest-posttest control group design. The sample of two classes with a total of 55 students, namely one experimental class (26 students) and one control class (29 students). Quantitative data for creative thinking variable were obtained by distributing tests and qualitative data and for learning motivation variable were obtained through questionnaires. Quantitative data were analyzed using non-parametric statistics (Mann-Whitney test) and qualitative data using the Percentage Mean Value formula. The quantitative research results show Asimp. Sig. (2-tailed)= 0.382 (>0.05). This means that H1 is rejected and H0 is accepted, which means there is no differences in the way students think creatively in the control class and the experimental class in science learning. The results of qualitative research show that students' learning motivation in the control class and the experimental class are both included in the very good criteria with the percentage in the range of 90.3% - 90.8%.